2000
DOI: 10.1046/j.1365-313x.2000.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific oxylipin signature of tomato flowers: allene oxide cyclase is highly expressed in distinct flower organs and vascular bundles

Abstract: A crucial step in the biosynthesis of jasmonic acid (JA) is the formation of its correct stereoisomeric precursor, cis(+)12-oxophytodienoic acid (OPDA). This step is catalysed by allene oxide cyclase (AOC), which has been recently cloned from tomato. In stems, young leaves and young flowers, AOC mRNA accumulates to a low level, contrasting with a high accumulation in flower buds, flower stalks and roots. The high levels of AOC mRNA and AOC protein in distinct flower organs correlate with high AOC activity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
131
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(149 citation statements)
references
References 100 publications
(118 reference statements)
14
131
0
4
Order By: Relevance
“…Furthermore, a distinct ratio of several octadecanoid-derived compounds, the so-called "oxylipin signature" may have a biological significance. For instance, such a signature was found to be different among various plant species (11) and attributed to distinct defense status (12), and varied also in the same species during development (13).…”
mentioning
confidence: 99%
“…Furthermore, a distinct ratio of several octadecanoid-derived compounds, the so-called "oxylipin signature" may have a biological significance. For instance, such a signature was found to be different among various plant species (11) and attributed to distinct defense status (12), and varied also in the same species during development (13).…”
mentioning
confidence: 99%
“…"Early genes", i.e., those rapidly induced after wounding, including those encoding prosystemin and some of the JA biosynthetic enzymes, are expressed in vascular bundles (Jacinto et al, 1997;Kubigsteltig et al, 1999;Hause et al, 2000), whereas "late genes", i.e., those for SWRPs with a direct role in plant defense, are expressed in palisade and adjacent spongy mesophyll cells (Shumway et al, 1976;WalkerSimmons and Ryan, 1977;Ryan, 2000). The temporally and spatially separated expression of the two classes of genes led to the suggestion that wound-signaling events may initially be activated in the vascular bundles to produce second messengers (octadecanoids, OGAs, H202) that will then induce defense gene expression in mesophyll cells (Orozco-Cárdenas, 2000;Ryan, 2000).…”
Section: The Role Of Tomato Systemin In Wound Signal Transductionmentioning
confidence: 99%
“…Creelman and Mullet (1997) reported that jasmonates are essential for the development of sink tissues during, for example, fruit ripening, the production of viable pollen and root growth. Further, mRNA of allene oxide cyclase (AOC), the key enzyme of Jasmonate biosynthesis, accumulates abundantly in sink tissues notably flower buds, flower stalks and roots (Hause et al 2000); expression was also shown to be induced by glucose. These data suggest that jasmonate biosynthesis may be induced by sugar imported to sink tissues and that newly synthesized jasmonates then may activate development of these tissues.…”
mentioning
confidence: 99%